Sequestration of Brilliant Green Dye by Coriander Leaf: Isotherm and Kinetic Studies - Mukherjee, Hemanta; Mukherjee, Soma (Trends in Sciences, 2022)
Adsorption process has been performed to investigate the potentiality of coriander leaf to sequester brilliant green (BG) dye from the aqueous phase. Coriander leaf of 75-micron size has been characterized by SEM, BET, FTIR etc. In the present study, emphasis has been given on the removal of BG dye under different conditions viz. dose of biomaterial (10.0 - 100.0 mg), pH (2.0 - 12.0) and dye concentration (10.0 - 100.0 mg/L) by Taguchi optimization. The batch experiments have been conducted at 25 ℃ with stirring speed of 120.0 rpm. The kinetic study is performed at two different temperatures, 30 and 40 ℃. The batch adsorption process for sequestration of the dye followed pseudo-2nd order kinetics (R2 = 0.99). The study also reveals that the Freundlich isotherm is the best fitted (R2 = 0.96) model. The adsorption capacity is 68.49 mg/g and the overall removal efficiency is above 80.0 %. HIGHLIGHTS The coriander leaf (75-micron) has been investigated as an effective adsorbent for Brilliant green dye in aqueous environment Effects of physico-chemical properties of adsorbent (BET, pZC, zeta potential, bulk density, moisture, ash etc.) and the role of several operating parameters (contact time, pH, dose and concentration) have been investigated Langmuir, Freundlich isotherm models and pseudo-second-order kinetic model favour the adsorption phenomena L9 orthogonal array (3X3) of Taguchi optimization study with ANOVA analysis predicts the role of control parameters GRAPHICAL ABSTRACT